UTILIZATION OF WILD RELATIVES OF WHEAT, BARLEY, MAIZE AND OAT IN DEVELOPING ABIOTIC AND BIOTIC STRESS TOLERANT NEW VARIETIES - Yumurtaci, Aysen (Emirates Journal of Food and Agriculture, 2014)
Dramatic changes in climatic conditions, exhibited as heat waves, water scarcity and heavy rains, continue to threaten crop quality and yield. Additionally, fungal-based plant pathogen booming is another reflection of climate change creating some potential risks for agricultural production of main staple crop species. Most of the abiotic and biotic stresses are under the control of complex traits. Moreover, a wide range of desirable quantitative characters in cultivated crops, such as disease resistance, might degenerate with time. Therefore, buffering crops against the large environmental changes is important for feeding the world’s increasing population and requires implementation of effective food security strategies. Crop biodiversity plays a key role in the improvement of stress tolerant species and enables an extensive platform for identification of novel traits by using a range of molecular tools. This offers homozygous crop models for the traits of interest, prediction models related to the stress tolerance and genetic resources for the transformation of cultivated crops. This review provides an overview for application of different crop wild relatives and demonstrates their roles on development of stress tolerant plants. It also highlights the importance of global crop conservation and alternative plant species for future plant breeding.